2012
DOI: 10.1007/s10964-012-9863-7
|View full text |Cite
|
Sign up to set email alerts
|

Bullies, Gangs, Drugs, and School: Understanding the Overlap and the Role of Ethnicity and Urbanicity

Abstract: Recent media attention has increased interest in behavioral, mental health, and academic correlates of involvement in bullying. Yet, there has not been much interest in investigating the co-occurrence of other health-risk behaviors, such as gang membership, weapon carrying, and substance use. The potential influence of contextual factors, such as youth ethnicity, urbanicity, and school characteristics, also has been overlooked in previous research. The current study examined different subtypes of involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
127
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 62 publications
7
127
1
13
Order By: Relevance
“…5 Previous studies have documented that African American race and Hispanic ethnicity are associated with increased likelihood of bullying and its associated mentaland physicalhealth impacts. 18,19,21 Our study also suggests that racial disparity persists for the risk of intentional injury-related EDVs. In addition to students of black race and Hispanic ethnicity, American Indian youth were found to be high risk.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…5 Previous studies have documented that African American race and Hispanic ethnicity are associated with increased likelihood of bullying and its associated mentaland physicalhealth impacts. 18,19,21 Our study also suggests that racial disparity persists for the risk of intentional injury-related EDVs. In addition to students of black race and Hispanic ethnicity, American Indian youth were found to be high risk.…”
Section: Discussionsupporting
confidence: 54%
“…This gender difference is interesting, especially because previous studies have identified male gender to be a risk factor for injuries in a variety of settings. 6,11,12,14,21,26 Further research is needed to understand why this disparity exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, underachievement has been shown to be a risk factor for being an aggressor and low involvement in school and lack of contact with teachers have been identified as risk factors for involvement in bullying [28][29][30].…”
Section: Discussionmentioning
confidence: 99%